2004
DOI: 10.1038/sj.ijir.3901231
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cavernosal smooth muscle dysfunction in low flow priapism using an in vitro model

Abstract: The effects of hypoxia (pO 2 : 50 mmHg), acidosis (pH: 6.9) or glucopenia (absence of glucose) in vitro on the tone of the rabbit corpus cavernosum were investigated. The recovery of smooth muscle contractility following exposure to these conditions was also assessed. Hypoxia, acidosis or glucopenia alone or in combination showed a sustained reduction in the tone. Reperfusion of tissue strips showed complete recovery of smooth muscle tone for all conditions except when hypoxia and glucopenia were combined or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 26 publications
4
67
0
Order By: Relevance
“…The maximum phenylephrine-induced contraction was reached within 10-20 s of application to CCSs from Ada + and Ada -/-mice. Electrical field stimulation (EFS) is commonly used to stimulate the nerves that innervate the smooth muscle cells of the corpus cavernosum to mediate smooth muscle relaxation, corresponding to normal physiological penile erection (12,27,28,30,31). In our studies, EFS induced relaxation of CCSs from both Ada + and Ada -/-mice in a voltage- and frequency-dependent manner ( Figure 1, B and C).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The maximum phenylephrine-induced contraction was reached within 10-20 s of application to CCSs from Ada + and Ada -/-mice. Electrical field stimulation (EFS) is commonly used to stimulate the nerves that innervate the smooth muscle cells of the corpus cavernosum to mediate smooth muscle relaxation, corresponding to normal physiological penile erection (12,27,28,30,31). In our studies, EFS induced relaxation of CCSs from both Ada + and Ada -/-mice in a voltage- and frequency-dependent manner ( Figure 1, B and C).…”
Section: Resultsmentioning
confidence: 76%
“…The particular EFS parameters of 0-30 V and 30 Hz, with a pulse width of approximately 0.5 ms, are commonly used in mice. Available evidence indicates that these electrical field strength parameters stimulate only neurons, not muscle, and thus are thought to mimic normal penile erection (27,28,31). The concentrations of cAMP and cGMP in CCSs were subsequently determined (see below).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was difficult to use rat CC strips in organ bath for mechanism studies, rabbit's CC strips were commonly used as described previously. 15,[20][21][22] It has been reported that nonginkgolide nonflavonoid fraction of ginkgo biloba extract (NGE) has the most potent relaxing effect on vascular smooth muscle. In the tissue precontracted by norepinephrine (10 À5 M), corpus cavernosal tissue of human and rabbit showed relaxation in response to subfractions of NGF in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on animal models have shown impaired response of cavernosal smooth muscle to sympathomimetic agents in the acidotic, hypoxic, and glucopenic conditions that develop during prolonged ischemia [6]. While at least one study reports safe resolution of ischemic priapism using high-dose phenylephrine (1,000 μg repeated every 5 min) [7], another suggests no benefit over conventional doses in cases of prolonged ischemia [8].…”
Section: Common Sympathomimetic Agentsmentioning
confidence: 99%